Maternal mortality in Brazil during the Covid-19 pandemic and post-pandemic period - Monteiro, Maria Joedna Ferreira; de Souza, Ana Cristina Henrique; Oliveira, Larissa Ellen de Souza; Viana, Alzenir Rosa; de Oliveira, Dayanne Rakelly (Seven Editora, 2024)
Maternal death occurs in the pregnancy-puerperal period due to causes directly linked to gestational conditions or by indirect causes resulting from pre-existing maternal conditions that worsen as a result of pregnancy. The coronavirus pandemic has posed a challenge for health care. The consequence of this was a considerable increase in the Maternal Mortality Ratio, reaching alarming values in the peak period of the pandemic. This study aims to identify the main causes of maternal death, which Brazilian regions obtained the highest values of deaths, and what is the period of the pregnancy-puerperal cycle in which these deaths occurred. This is an ecological, descriptive and quantitative analytical study built using data from the DataSus Information System in the period from 2019 to 2022. MMR increased significantly during the pandemic, especially in 2021. The Southeast and Northeast regions recorded the highest numbers of maternal deaths. Maternal mortality causes were divided into direct (complications of pregnancy, childbirth, or puerperium) and indirect (pre-existing conditions aggravated by pregnancy), with a notable increase in indirect causes during the pandemic. Maternal mortality rates were highest among women aged 20 to 39 years, highlighting a significant vulnerability in this age group. Regional and socioeconomic inequalities were critical factors, with black women having the highest mortality rates. The lack of access to adequate health care during the pandemic exacerbated the situation, preventing prenatal, childbirth and postpartum care, which is essential for maternal health. DOI:https://doi.org/10.56238/sevened2024.018-072